Abundant Exact Solition-Like Solutions to the Generalized Bretherton Equation with Arbitrary Constants - Xiuqing Yu; Fengsheng Xu; Lihua Zhang (Abstract and Applied Analysis)
The Riccati equation is employed to construct exact travelling wave solutions to the generalized Bretherton equation. Taking full advantage of the Riccati equation which has more new solutions, abundant new multiple solition-like solutions are obtained for the generalized Bretherton equation.